2016
DOI: 10.1515/zpch-2016-0882
|View full text |Cite
|
Sign up to set email alerts
|

Graded Shells in Semiconductor Nanocrystals

Abstract: Abstract:The current state-of-the-art of the fabrication and photophysics of graded shells in quantum dots is reviewed. Graded shells, i.e. partially alloyed interfaces between core and shell or between two shells of semi conductor nanoheterostructures, have been demonstrated to improve fluorescence properties and suppress non-radiative pathways of exciton dynamics. By simply looking at linear optics on the level of single excitons this is reflected in increased photoluminescence quantum yields. However, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…One can clearly see that the fwhm value was not altered after the 4 ML shell growth, as compared to that of the initial core sample (the two x -axes have been shifted for superposition of the peaks). This observation suggests the preservation of the standard size deviation of the heterostructured NCs under the employed synthesis conditions, a result which is almost unattainable by means of other shell growth techniques . The data presented in Table reveals that the growth process is quite homogeneous, although for some shell compositions we can notice slight broadening of the PL spectra during c-ALD.…”
Section: Resultsmentioning
confidence: 99%
“…One can clearly see that the fwhm value was not altered after the 4 ML shell growth, as compared to that of the initial core sample (the two x -axes have been shifted for superposition of the peaks). This observation suggests the preservation of the standard size deviation of the heterostructured NCs under the employed synthesis conditions, a result which is almost unattainable by means of other shell growth techniques . The data presented in Table reveals that the growth process is quite homogeneous, although for some shell compositions we can notice slight broadening of the PL spectra during c-ALD.…”
Section: Resultsmentioning
confidence: 99%
“…Boldt et al observed a redshift during heating CdSe/CdS/ZnS core/ multishell QDs at 310 °C, and attributed it to the formation of CdSe/Cd x Zn 1¹x S core/graded shell structure due to interfacial alloying. 40,41 While alloying at the type I core/shell interface typically results in an increased bandgap for the core, the graded composition creates a stepless band-edge potential curve, which broadens the electron wavefunction. If this broadening effect is more pronounced than the increase in the core's bandgap, a redshift would occur.…”
Section: Discussionmentioning
confidence: 99%
“…Slejko et al carried out an important study on Cd­(Zn)S shell growth by colloidal atomic layer deposition (c-ALD) on CdSe nanocrystals. This technique developed by Ithurria et al results in uniform-layer-structured shells and allows the conservation of the size distribution of the NPLs, unlike other shell growth methods. , The authors followed the shell growth by measuring the UV–vis absorption and PL spectra of their CdSe core–Cd­(Zn)S shell nanocrystals after the deposition of each atomic layer and could obtain important information on the structural aspects of stepwise shell formation. However, they used spherical quantum dots in their study , that are known to expose several different crystal surfaces .…”
Section: Introductionmentioning
confidence: 99%